TITIK-ANTARA DI DALAM RUANG METRIK DAN RUANG INTERVAL METRIK - Talakua, Mozart W. (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2007)
A point p in metric space ()dX, is called a between-point of if Xbaâˆˆ,()()(bpdpadbad,,,+= ). This concept was formulated by Menger in 1928. If all the between-points of a and b is collected in a set, then a and b are that set automaticlly. In the metric space ()dX, and if there are operator in X, hence this interval operator is called metric interval operator. The couple of () is called metric interval space.